Understanding the Coins of Bengal : Ancient to Early Modern Period - Islam, Shariful (Brill | Manohar Publishers & Distributors, 2019)
This volume helps in understanding coins issued by different dynasties and kingdoms of Bengal from ancient to the early modern period. It provides illustrations of legends and in particular cases images or figures on both sides of coins. Though this work is not an attempt to document new information to the history of Bengal, a couple of new numismatic discoveries have been discussed in the volume. The focal point of the volume is on the coins that were in use as money in Bengal during Magadha Janapada, Gupta dynasty, Pala era, Harikela and Akara kingdoms, Sultanate and Nawabs' period and finally the early East India Company period. A few coins of the neighbouring kingdoms, have also been illustrated in the last chapter as they are supposed to have been in use in at least some parts of Bengal because of political, topographical and/or other reasons.This volume would be of immense interest to scholars of South Asian numismatics and the history of the two Bengals.